IMPORTANCE OF THE PACKAGING FOR THE MARKETING OF GREEN ONIONS (ALLIUM FISTULOSUM) IN BOYACÁ - Vanegas Dueñas, Rudy Ronaldo
Due to the economic potential of the department of Boyacá in relation to the cultivation of Green onions (Allium fistulosum) or junca which is 195,358 tons, corresponding to 67.4% of the total production of the country. The implementation of adequate packaging in order to preserve the vegetable for longer, minimizing transport damages and providing added value by expanding its markets while conserving its organoleptic characteristics, is relevant for the productive sector of the department of Boyacá. The objective of this article is to provide information about current post-harvest processes implemented by producers, evidencing the possible losses of the vegetable caused by the handling observed in the field works carried out in the municipality of Aquitania Boyacá. And also the packaging alternative using modified atmosphere technology and the advantages of its implementation for the sector. The implemented methodology consist of collecting information in primary and secondary bibliographic sources such as scientific articles, web platforms and field visits made directly to the crops in cooperation with the association named Parcela as a source of participant observation. As a result, it was observed a minimal use of package and packaging by producers and their preference for traditional practices that do not allow to generate value to the harvested product, limiting to marketing and sale in storage centers or intermediaries. The packaging technology using modified atmosphere is important for preserving the product. In this way it extends its lifetime, minimizes the loss of quality and conserves its organoleptic characteristics; Likewise, this package reduces damages caused by transportation. these implementations contribute to a considerable improvement in its production chain adding value to the product.